The cultural capital of Shakespeare's Hamlet in Haider - Abigail Shantini K. (Nanyang Technological University, 2022)
This project explores the concept of cultural capital in relation to Haider, a Hindi film adaptation of Shakespeare's Hamlet. It attempts to understand and exhibit Hamlet's symbolic resonance and show how adaptations of Hamlet add to the source text, bringing previously underemphasized parts of the work to the forefront. This thesis uses the forms of cultural capital, namely institutionalized, objectified, and embodied cultural capital as tools in which to understand the expressions of power, love, and loss in Haider. In closely comparing Hamlet and Haider, I show how the sagacity of Haider lies in its deft departures from the source text, whilst still embodying the essence of the work. In turn, this thesis aims to show how the relationship between adaptation and source text is more symbiotic than parasitic, though the two works function as separate entities. In showing this relationship, readers are bearing witness to the reclaiming of narratives, allowing individuals to build for themselves a home where there was none.